(untitled) (Bangladesh Journal of Agriculture, 2022)
Drought is a major abiotic constraint for growing rainfed rice in Bangladesh. A set of 18 boro rice genotypes were evaluated under irrigated and rainfed conditions to identify the high yielding and stress tolerant genotypes. The experiment was conducted by using randomized complete block design with three replications. Significant variations were observed among the genotypes both in irrigated and rainfed conditions. The genotypes BRRI dhan55, Gopal Deshi and Soilerpona showed the superior performance in terms of grain yield and yield contributing characters under rainfed condition. Based on stress tolerance index (STI) value, the genotypes BRRI dhan55, BRRI dhan58, Soilerpuna and Gopaldeshi were graded as drought tolerant genotypes. Under rainfed condition, yield per plant showed the positive and significant correlation with flag leaf length, number of primary branches per panicle, number of secondary branches per panicle, number of grains per panicle and thousand-seed weight. Path analysis revealed that the number of primary/secondary branches per panicle, and number of unfilled grains per panicle showed the highest positive and direct effect on grain yield under irrigated condition while Plant height, panicle length and thousand-seed weight had the highest direct but negative effect on grain yield.Thousand seed weight, number of primary branches per panicle and number of unfilled grains per panicle showed the highest positive and direct effect on grain yield under rainfed condition. Based on the results, seven genotypes from among the eighteen tested namely BRRI dhan36, BRRI dhan55, BRRI dhan58, BRRI dhan59, Soilerpona, Gopal Deshi and Borail were identified as drought tolerance genotypes with high yield potential. Bangladesh J. Agri. 2019-2021, 44-46: 77-87